State- and Condition-Dependent Modulation of the Hindlimb Locomotor Pattern in Intact and Spinal Cats Across Speeds - Harnie, Jonathan; Audet, Johannie; Mari, Stephen; Lecomte, Charly G.; Merlet, Angèle N.; Genois, Gabriel; Rybak, Ilya A.; Prilutsky, Boris I.; Frigon, Alain (Frontiers in Systems Neuroscience, 2022)
Locomotion after complete spinal cord injury (spinal transection) in animal models is usually evaluated in a hindlimb-only condition with the forelimbs suspended or placed on a stationary platform and compared with quadrupedal locomotion in the intact state. However, because of the quadrupedal nature of movement in these animals, the forelimbs play an important role in modulating the hindlimb pattern. This raises the question: whether changes in the hindlimb pattern after spinal transection are due to the state of the system (intact versus spinal) or because the locomotion is hindlimb-only. We collected kinematic and electromyographic data during locomotion at seven treadmill speeds before and after spinal transection in nine adult cats during quadrupedal and hindlimb-only locomotion in the intact state and hindlimb-only locomotion in the spinal state. We attribute some changes in the hindlimb pattern to the spinal state, such as convergence in stance and swing durations at high speed, improper coordination of ankle and hip joints, a switch in the timing of knee flexor and hip flexor bursts, modulation of burst durations with speed, and incidence of bi-phasic bursts in some muscles. Alternatively, some changes relate to the hindlimb-only nature of the locomotion, such as paw placement relative to the hip at contact, magnitude of knee and ankle yield, burst durations of some muscles and their timing. Overall, we show greater similarity in spatiotemporal and EMG variables between the two hindlimb-only conditions, suggesting that the more appropriate pre-spinal control is hindlimb-only rather than quadrupedal locomotion.